2016
DOI: 10.1186/s11671-016-1422-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Copper And Zinc Nanoparticles on the Growth Parameters, Contents of Ascorbic Acid, and Qualitative Composition of Amino Acids and Acylcarnitines in Pistia stratiotes L. (Araceae)

Abstract: The paper covers the research of copper and zinc nanoparticle effect on the content of ascorbic acid, and quantitative and qualitative composition of amino acids and acylcarnitines in Pistia stratiotes L. plants. Plant exposition to copper nanoparticles led to the decrease in (1) the amount of ascorbic acid, (2) the total content of amino acids (by 25 %), and (3) the amount of all studied amino acids except for the glycine amino acid. At this, the amount of 5-oxoproline, arginine, leucine, ornithine, phenylala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 20 publications
2
15
1
Order By: Relevance
“…Carbohydrate is positively correlated with Ca (0.642 ** ). In the present study though the protein content was high in most of the treatment but it was negatively correlated with Ca and Cu content but the result was disagreed with Ashok et al (2016) and Olkhovych et al (2016) who found that protein content was positively correlated with copper in different sorghum species and in Pistia stratiotes respectively. Iron content was positively correlated with Mg and Ca suggesting the possibility of combining selection for both micronutrients the result agreed with Ashok et al (2016) who reported that Mg and Ca content increases with Iron in different sorghum species.…”
Section: Minor Mineralscontrasting
confidence: 98%
“…Carbohydrate is positively correlated with Ca (0.642 ** ). In the present study though the protein content was high in most of the treatment but it was negatively correlated with Ca and Cu content but the result was disagreed with Ashok et al (2016) and Olkhovych et al (2016) who found that protein content was positively correlated with copper in different sorghum species and in Pistia stratiotes respectively. Iron content was positively correlated with Mg and Ca suggesting the possibility of combining selection for both micronutrients the result agreed with Ashok et al (2016) who reported that Mg and Ca content increases with Iron in different sorghum species.…”
Section: Minor Mineralscontrasting
confidence: 98%
“…The noticed increase in protein concentration in plants exposed to Cu and Zn NPs by Olkhovych et al (2016) was confirmed with the present results that showed an increase in the soluble protein content in the S. nigrum callus under different concentrations of ZnO NPs. Furthermore, Priyanka & Venkatachalam (2016) suggested that improvements in the soluble protein content may protect cells from oxidative stress caused by ZnO NPs.…”
Section: Effects Of Zno Nps On Amino Acids Soluble Proteins and Carsupporting
confidence: 91%
“…Finally, a reduction in ascorbic acid level in fruits treated with biostimulants containing zinc (ZIN and SIL) was recorded (Table 11). This effect might be due to the inhibitory action of selected metals (e.g., zinc and copper) on the enzyme activity of ascorbic acid metabolism as also shown by Olkhovych et al [80] on other species.…”
Section: Discussionmentioning
confidence: 74%